2011
DOI: 10.1515/polyeng.2011.061
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of polymers by additives and irradiations and their characterizations

Abstract: Polymer properties are often engineered in desired directions by additives or by irradiations or by both. However, in space and certain other applications, energetic particles or γ -rays may damage the polymeric parts in undesired directions, needing prior radiation damage studies for necessary precautions. Case studies of three completely different polymeradditive composites follow: (1) shielding e lectro m agnetic i nterference (EMI) by different composites of a polymeric binder, (2) electrical, thermal, mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…Therefore, ions can migrate in the amorphous region. The dominance of darker portion which is amorphous was also confirmed by many other scientists 38,39…”
Section: Resultssupporting
confidence: 61%
“…Therefore, ions can migrate in the amorphous region. The dominance of darker portion which is amorphous was also confirmed by many other scientists 38,39…”
Section: Resultssupporting
confidence: 61%
“…At higher dose, the conductivity drops down and the matrix retains its original backbone, therefore, the variation in conductivity can be attributed to the variation in the number of charge carriers due to possible cutting of the chains. It is reported that the low dose of the ions cut the long chain and create regions of local increased amorphicity, but at higher dose exposure may cause the release of hydrogen and hence carbonization of polymer films may also occur [124,125]. The fluence of the ion beam was gradually increased up to the limit where the backbone of the polymer film does not collapse and hydrogen is released from the chain.…”
Section: (E) Pvp+ Nai With Carbon Beam (C 5+ ) At 50 Mevmentioning
confidence: 99%
“…This energy is equally distributed into two oppositely emitted photons (each of energy 511 keV in the electron-positron centre of mass) to meet the criteria of momentum conservation. The start-stop coincidence γ-spectrometer detects the 1.27 MeV photon as the start and one of the two 511 keV photons as the stop for a time to pulse height (TPH) analyzer [181]. The time difference between the occurrences of these two events is measured as the lifetime of the positron and the lifetime spectrum N(t) vs. t is recorded by a multi channel analyzer or a computer.…”
Section: Positron Annihilation Spectroscopy (Pas) Positron Annihilati...mentioning
confidence: 99%